2016
DOI: 10.1002/pmh.1352
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient psychodynamic group psychotherapy – outcomes related to personality disorder, severity, age and gender

Abstract: Psychodynamic group psychotherapy is a recommendable treatment for moderate PDs, which may address avoidant strategies, but may not meet clinical challenges of borderline PD. The outcome differences related to gender and age are noteworthy. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Firstly, the qualitative interviews of female drop‐out patients with BPD (Hummelen et al ., ) indicated a distressing experience of strong negative emotions in a psychodynamic group setting. Secondly, a more recent quantitative study including patients with BPD in stand‐alone, outpatient psychodynamic group therapy, associated early drop‐out with enhanced symptom distress and troubling experience of the group climate (Kvarstein et al ., ). Thirdly, an RCT, which compared long‐term effects of a group‐based step‐down treatment programme (as PDT) to individual therapy, suggested that the group‐based treatment was challenging for patients with more severe psychopathology.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Firstly, the qualitative interviews of female drop‐out patients with BPD (Hummelen et al ., ) indicated a distressing experience of strong negative emotions in a psychodynamic group setting. Secondly, a more recent quantitative study including patients with BPD in stand‐alone, outpatient psychodynamic group therapy, associated early drop‐out with enhanced symptom distress and troubling experience of the group climate (Kvarstein et al ., ). Thirdly, an RCT, which compared long‐term effects of a group‐based step‐down treatment programme (as PDT) to individual therapy, suggested that the group‐based treatment was challenging for patients with more severe psychopathology.…”
Section: Discussionmentioning
confidence: 97%
“…High comorbidity of symptom disorders may also indicate more severe personality pathology (Zanarini, Frankenburg, Hennen, et al., ; Zimmerman et al ., ).Patients with BPD can be extensive users of health services (Bode, Vogel, Walker, & Kroger, ; Frankenburg & Zanarini, ). However, health service reports also include poor compliance, treatment drop‐out, and repeated experiences of treatment failures (Barnicot, Katsakou, Marougka, & Priebe, ; Kvarstein & Karterud, ; Kvarstein, Karterud, & Pedersen, ; Kvarstein, Nordviste, Dragland, & Wilberg, ). Such treatment irregularity is likely to be linked to core BPD pathology (Hummelen, Wilberg, & Karterud, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therapist alliance, engagement and confidence within the group setting are basic elements in a group therapy process. Monitoring therapy experience is a central issue in PD treatment . Poor treatment adherence is an often described central challenge of Borderline PD …”
Section: Discussionmentioning
confidence: 99%
“…In this first study, our aim was to construct an instrument measuring specific effects of art therapy on patients with a PD cluster B/C. We focused on patients with PD cluster B and/or C, because these PD clusters are the most prevalent and common group‐based treatment programmes for PD often recruit poorly functioning patients covering a range of personality pathology . A large part of the art therapists work with this target group, and despite the consensus on this, there is little evidence about the added value.…”
Section: Study 1: Scale Development and Confirmationmentioning
confidence: 99%
See 1 more Smart Citation